Growth and Yield Response of Sunflower (Helianthus annuus L.) Plants to Paclobutrazol Dosage and Application Time - Fitriyah Fitriyah; Ramdan Hidayat; Widiwurjani Widiwurjani (The University of Lampung, 2025)
Sunflower (Hellianthus annuus L.) has high economic value due to its great potential in industry. High market demand causes the need for intensification in sunflower cultivation to increase production and seed quality. This study aims to determine the right dosage and time of paclobutrazol application in suppressing growth and increasing the yield of sunflower plants. The research was conducted in Dohoagung Village, Balongpanggang District, Gresik Regency from May to September 2024. This research used a Factorial Completely Randomized Design (CRD) with 2 factors, namely dose and application time. The two treatments resulted in 12 combinations, each of which was repeated three times. The results of the analysis of variance were further tested with the 5% HSD test. The results show that the combination of paclobutrazol dosage of 0.3 g/plant and application time of 4 WAP gives the best results on plant growth (plant height and stem diameter). The single treatment of paclobutrazol dosage of 0.2 g/plant gave the best results on flower diameter, number of seeds, total seed weight and 100 seed weight. A single treatment of paclobutrazol application time at 4 WAP produced the best plant growth and increased flower diameter.